Trade policy, the price of capital goods and econoomic growth: An empirical test of a Solow-Swan model with capital variety - Rainer Maurer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
In this paper I test the hypothesis that trade policies leading to higher prices for capital goods have a negative influence on the steady state level and transitional growth rate of per capita GDP. I derive this hypothesis from a modified version of a Solow-Swan model, in which capital variety increases productivity. This model has the implication that import restrictions on foreign capital goods reduce the steady state level and the transitional growth rate of per capita GDP. However, although I assume that technological progress spreads over different countries via the import of new capital goods, import restrictions do not reduce the steady state growth rate. A reduction of the steady state growth rate is only possible, if the number of varieties of imported capital goods were restricted. The empirical results show that capital goods prices as well as the relative input ratios of domestic and foreign capital goods are significantly positively affected by the level of import tariffs on capital goods and the coverage ratio of non-tariff measures on capital goods. A test of the steady state version of the Solow-Swan model displays a statistically significant negative relation between import restrictions on foreign capital goods and the level of per capita GDP. A test of the transitional version of the Solow-Swan model displays a statistically significant negative relation between import restrictions on foreign capital goods and the transitional growth rate of per capita GDP.
Keywords: 330; Trade policy; economic growth of open economies; neoclassical growth theory; new growth theory; empirical test; Wachstumstheorie; Zoll; Protektionismus; Investitionsgut; Import; Kapitalintensität; Neue Wachstumstheorie; Schätzung; Theorie